Armed Conflict, Military Expenses and FDI Inflow to Developing Countries. Issue 2 (23rd February 2019) - Aziz, Nusrate; Khalid, Usman
Abstract: This paper investigates the relationship between military expenditure and FDI inflow conditioning on the exposure of a country to armed conflict in the long run. We apply the band spectrum regression estimator, and the maximal overlap discrete wavelet transform, to a panel of 60 developing countries, for the years 1990 to 2013. The estimated results indicate that military expenditure, in the absence of armed conflict, reduces FDI inflow. However, the negative effect is mitigated by increased military expenditure, in the presence of armed conflict. We also show that the effect of military expenditure on FDI is time sensitive, in that it takes time for military expenditure to affect FDI inflow. FDI inflow in response to higher military expenditure is higher for the country that faces higher armed conflict than the country that faces lower armed conflict. The findings are robust in the case of overall as well as internal conflict. These results are also robust to the alternative specification, subsample analysis with different armed conflict thresholds, and the estimation using the time variant long-run models.